Research on the Transformation of User's Implicit Knowledge to Design Knowledge in Product Design - Sun Qiang; Hu Fei (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The characteristics of the user’s implicit knowledge in product design and the relationship between the user’s implicit knowledge and design knowledge are discussed. The transformation model of user implicit knowledge to design knowledge is built. And the key technologies of it are analyzed. The four design dimensions which the transformation from user implicit knowledge to design knowledge is based on are proposed, namely, the design process dimension, the design object dimension, the organization dimension and the knowledge dimension. Taking household cleaner as an example, this paper utilizes the oral analysis method and the semantic differential method to analyze the transformation of user implicit knowledge to design knowledge, and validates the conversion model. It is helpful for improving the computer aided industrial design and household appliance products network collaborative design.